Sustained Effect of Music Training on the Enhancement of Executive Function in Preschool Children - Shen, Yue; Lin, Yishan; Liu, Songhan; Fang, Lele; Liu, Ge (Frontiers in Psychology, 2019)
Musical training is an enrichment activity involving multiple senses, including auditory, visual, somatosensorial, attention, memory, and executive function (EF), all of which are related to cognition. This study examined whether musical training enhances EF in preschool children who had not undergone previous systematic music learning. This study also explored the after-effects 12 weeks after cessation of musical training. Participants were 61 preschool children from a university-affiliated kindergarten in North China. The experimental group underwent 12 weeks of integrated musical training (i.e., music theory, singing, dancing, and role-playing), while the control group performed typical daily classroom activities. The 3 components (inhibitory control, working memory, cognitive flexibility) of executive functions were evaluated using the Day/Night Stroop, Dimensional Change Card Sort, Dot Matrix Test, and Backward Digit Span Task. In Experment 1, EFs were tested twice-before (T1) and after (T2) the music training. The results showed that children’s EFs could be promoted by musical training. In addition, EFs were tested again 12 weeks later after the end of the intervention (T3) in Experment 2. We discovered that integrated musical training demonstrated a sustained promotion effect.